Pengaruh Return On Assets, Debt To Equity Ratio dan Earning Per Share Terhadap Price To Book Value Pada Perusahaan Perbankan yang Terdaftar Di Bursa Efek Indonesia Pada Periode Tahun 2015-2018 - Cindy; David; Lilia; Santitra; Rico (Jurnal Manajemen Bisnis Eka Prasetya, 2020)
Price to Book Value is a form of scale assessment that measures Shareholder’s wealth. The purpose of research is to test and analyze the influence of Return on Assets, Debt to Equity Ratio and Earning Per Share against Price to Book Value on Banking Company registered on Indonesia Stock Exchange on the period 2015-2018. Theory used are the theories that have a relation with Return on Assets, Debt to Equity Ratio and Earning Per Share against Price to Book Value. This research Using quantitative approaches with types of descriptive research and the nature of research Explanatory. The population of this research is 43 registered companies in IDX. Sample of This study as many as 28 companies where samples were obtained from the process purposive Sampling that meets certain criteria. Research results can be concluded that The simultaneous Return on Assets, Debt to Equity Ratio and Earning Per Share are influential Against Price to Book Value with a signed value (0.002 < 0.05). Partial Return on Assets affect Price to Book Value while Debt to Equity Ratio and Earning Per Share has no effect on Price to Book Value.